Efektifitas Senam Lansia Terhadap Penurunan Tekanan Darah Pada Lansia Hipertensi Di Wilayah Kerja Puskesmas Bulu Kabupaten Sukoharjo - ZULAIKHA, IKHA, Heru Subaris Kasjono, SKM., M, Anisa Catur Wijayanti, SKM (2016)
Health problems that are often experienced by the elderly one of which is hypertension. One way to lower blood pressure with the elderly gymnastics. Elderly gymnastics is a sport that is lightweight and easy to do, but not onerous which is applied to the elderly. This study aims to determine the effectiveness of gymnastics elderly to decrease blood pressure in elderly hypertensive in Puskesmas Bulu. This type of research is a quasi-experimental design approach to non-randomized control group pre-test post-test design. The population in this study were all elderly with hypertension in Puskesmas Bulu. The sample selection using purposive sampling technique, which consists of 10 experimental group 1 with exercises 2 times a week, 9 in the experimental group 2 with exercise 3 times a week and 9 elderly control group without exercise. The results of the analysis using Kruskal Wallis test showed that there are differences in systolic blood pressure in all three study groups (p=0,028), but there was no difference in diastolic blood pressure in all three study groups (p=0,367).